Emission control of NOx precursors during sewage sludge pyrolysis using an integrated pretreatment of Fenton peroxidation and CaO conditioning. (1st May 2017) - Liu, Huan; Yi, Linlin; Hu, Hongyun; Xu, Kai; Zhang, Qiang; Lu, Geng; Yao, Hong
Graphical abstract: Highlights: A novel integrated sludge pretreatment method was proposed to control NOx emission. Iron conditioner prevented some N-containing organics of sludge from deamination. Active Fe derived from conditioner reacted with NH3 through the formation of Feα N. Composite conditioner reacted with protein-N and char-N to form Feα N and CaCx Ny . Ca2 Fe2 O5 formation facilitated the decomposition of Feα N and CaCx Ny to release N2 . Abstract: In order to control the emissions of NOx precursors during sewage sludge pyrolysis, we proposed a novel integrated pretreatment method based on Fenton peroxidation and CaO conditioning. Nitrogen transformation was investigated using a self-designed drop-tube/fixed-bed furnace, and the mechanism of influence of residual conditioners was further clarified by employing model compounds. According to the results, the conversion of sludge- N to gas- N at 873–1273 K was strengthened by composite conditioning during the pyrolysis process. The remaining iron salts prevented some nitrogenous organic matter from deamination, whereas calcium compounds promoted the decomposition of proteins and amine to release NH3 . Active iron atoms derived from an Fe-bearing conditioner reacted with NH3 through the formation of Feα N. Furthermore, combined conditioning hampered the conversion of amine- N /pyridine- N, pyrrole- N and nitrile- N to HCN, therefore enhancing their yields in char. The residual Ca compounds, which presented as Ca(OH)2, facilitated the hydrolysis of HCN and hampered HCN generation from amine- N, nitrile- N and heterocyclic- N in tar. Both residual iron and calcium conditioners were capable of reacting with protein- N in sludge and char to form Feα N and CaCx Ny, respectively. The formation of complex Ca2 Fe2 O5 facilitated the decomposition of these intermediates, thus facilitating the conversion of sludge- N and NOx precursors (tar- N, NH3, HCN) to N2, achieving a highest non-polluting gas yield of 80.5%.